Implementation of the unified theory of acceptance and use of Technology (UTAUT) model during the pandemic era: A systematic literature review (SLR) - Evie Ariadne Shinta Dewi; Zuhairi Sanofi; Benazir Bona Pratamawaty; Hadi Suprapto Arifin (Penerbit Universiti Kebangsaan Malaysia, 2023)
The pandemic's unique situation has sparked interest for investigation, particularly in understanding ICT user behavior using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This article presents a systematic literature review (SLR) aiming to identify UTAUT model applications during the pandemic, explore contexts and methods used, assess global involvement, and understand factors influencing ICT adoption. Following the Reporting standards for Systematic Evidence Syntheses (ROSES) protocol, 70 articles were comprehensively analyzed out of 801 obtained from Scopus, ScienceDirect, and Google Scholar. The review revealed 249 researchers from 44 countries conducting empirical studies on ICT adoption with UTAUT during the pandemic. Dominant contexts were education, healthcare, and mobile technology. Notably, confirmed performance expectancy emerged as the main factor influencing ICT adoption intention, supported by 48 studies (68.57%). Additionally, facilitating conditions' effects were confirmed by 37 studies (52.86%), while effort expectancy and social influence effects were each confirmed by 35 studies (50%). The findings underscore the importance of education, healthcare, and mobile technology during crises, urging attention from governments, policymakers, technology managers, and academics. Individuals demonstrated strong motivation to utilize technology for work facilitation, regardless of resource availability, knowledge, comfort, or social influence from the newly adopted systems or technologies during the pandemic. Furthermore, countries affected by the pandemic could adopt successful systems or technologies from researchers' home countries to foster ICT adoption during future crises.